Penggunaan Model 4D dalam Pembuatan Video Tutorial Menggambar Alam Benda di SMP Negeri 1 Tonra - A Rafida; Abd Aziz Ahmad; Ali Ahmad Muhdy (Universitas Negeri Makassar, 2022)
This research aims to describe the development of video tutorials for learning to draw natural objects for students of class VII SMPN 1 Tonra. This research is a type of research and development (R&D). Development models use 4D models consisting of Define (definition), Design (design), Develop (development), Dissemination (dissemination). But in this study it only reached the stage of Develop. From the results of assessments or validations conducted by material experts and media experts on the resulting video tutorial media, obtained a rating score of 95.15% from material experts, and 89.7% from media experts. Based on the results obtained, it can be concluded that the video tutorial media for learning to draw nature is worth using and developing, and is expected to help teachers and students in the learning process.Keywords: learning media, video tutorials, drawing natural objects. AbstrakPenelitian ini bertujuan untuk mendeskripsikan pengembangan video tutorial untuk pembelajaran menggambar alam benda bagi peserta didik kelas VII SMPN 1 Tonra. Penelitian ini merupakan jenis penelitian dan pengembangan atau Research and Development (R&D). Model pengembangan menggunakan model 4D yang terdiri dari Define (pendefinisian), Design (perancangan), Develop (pengembangan), Dissemination (penyebarluasan). Namun pada penelitian ini hanya sampai pada tahap Develop. Dari hasil penilaian atau validasi yang dilakukan oleh ahli materi dan ahli media terhadap media video tutorial yang dihasilkan, diperoleh skor penilaian sebesar 95,15% dari ahli materi, dan 89,7% dari ahli media. Berdasarkan hasil yang diperoleh, maka dapat disimpulkan bahwa media video tutorial untuk pembelajaran menggambar alam benda ini layak digunakan dan dikembangkan, serta diharapkan dapat membantu pendidik dan peserta didik dalam proses pembelajaran.Kata kunci : media pembelajaran, video tutorial, menggambar alam benda.